The Role of Social Media in Increasing Sales on E-Commerce Platforms - Titi Wideratna; Dimas Nurdiansyah; M.Rakha Mughits; Rafa Fitria Hidayat; Zahrani Zanna Manap; Wulan Tri Fatonah; Rigi Ibrahim; Megan Dani Dinaharja; Siti Nur Syaidah; Bunga Ameli Putri (LPPM STMIK Mardira Indonesia, 2025)
This community service initiative seeks to improve the community's understanding and proficiency in using digital technology, specifically in online marketing through e-commerce and the Shopee Affiliate network. The seminar is intended to address the persistently poor digital literacy among micro-entrepreneurs and the general populace in effectively utilizing e-commerce platforms. Participants gain foundational knowledge of e-commerce principles, digital marketing tactics, and the procedural steps necessary to engage and generate revenue through the Shopee Affiliate program via outreach and practical sessions. The implementation methods include interactive lectures, group discussions, and practical exercises using digital devices. The activity's results indicate a substantial enhancement in participants' understanding of e-commerce and affiliate marketing, along with a renewed impetus to investigate online business prospects. This effort aims to enhance the community's economic independence and competitiveness in the digital age.